Hubungan antara Penggunaan Media Sosial, Aktivitas Fisik dan Tingkat Stres Terhadap Status Gizi Usia 18 – 25 Tahun Di RW.03 Kelurahan Kebayoran Lama Utara - Faridi, Ahmad; Vidyarini, Andra; Syifa, Nisrina (HB PRESS, 2024)
Nutritional problems in adults are affected by the use of social media which results in increased sedentary activity which can cause nutritional problems and increased stress levels. The increase in stress levels affects the increase in food intake so it can affect nutritional status. The general purpose of this study was to analyze the relationship between social media usage, physical activity, stress levels and nutritional status of adults in 3rd Hamlet North Kebayoran Lama, South Jakarta. This type of research is quantitative study with cross-sectional design approach. Primary data collected in this study included nutritional status, social media usage, physical activity, and stress levels in age 18 – 25 years in 3rd Hamlet North Kebayoran Lama, South Jakarta. Secondary data was obtained from journals, articles, literature, and sites related to research. The sample for this study was 63 residents who were selected by purposive sampling according to inclusive and exclusive criteria. Chi Square was used to analyze the data. The results of this study revealed that there was no relationship between the use of social media and nutritional status (p = 0.223), there was no relationship between physical activity and nutritional status (p = 0.181), there was a relationship between stress levels and nutritional status (p = 0.005). From this study, it was concluded that there is relationship between stress levels and nutritional status in age 18 – 25 in 3rd Hamlet North Kebayoran Lama.